2016
DOI: 10.1111/pde.12881
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Premature Hair Graying in Young Turkish Adults

Abstract: PHG is closely related to factors causing oxidative stress, such as emotional stress, alcohol consumption, and chronic diseases in genetically predisposed men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
14
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 16 publications
(30 reference statements)
6
14
2
Order By: Relevance
“…There are few studies evaluating risk factors associated with PHG in the literature. In these studies, smoking, alcohol consumption, family history of PHG, emotional stress, obesity, and atopy were reported to be associated with PHG . In our study, vegetarian diet preference, atopy history, and family history of PHG were significantly higher in subjects with PHG.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…There are few studies evaluating risk factors associated with PHG in the literature. In these studies, smoking, alcohol consumption, family history of PHG, emotional stress, obesity, and atopy were reported to be associated with PHG . In our study, vegetarian diet preference, atopy history, and family history of PHG were significantly higher in subjects with PHG.…”
Section: Discussionsupporting
confidence: 55%
“…Genetic inheritance of PHG is thought to be autosomal dominant. Some studies reported that family history of PHG was higher in subjects with PHG . In a study including 6392 Korean men who were younger than 30 years old, PHG prevalence was determined as 25.3%.…”
Section: Discussionmentioning
confidence: 97%
“…Decreased hair tip pigmentation detected in exam students at T2 therefore appears to be a promising surrogate indicator of hampered hair growth in a stressed healthy human. In addition, it may indicate oxidative stress [72] and the onset of premature graying [96]. Some changes in hair measures were however also observed in the comparison group between T1, T2 and T3 and no T2 group differences were found.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have uncovered tantalizing clues to the identity of the target molecule that PKA modifies by the addition of a phosphate group (phosphorylation). However, proposals for specific candidate targets, phosphorylation sites [8][9][10] and modulatory mechanisms have been repeatedly called into question by further tests, including some in painstakingly constructed mouse models [11][12][13] . Liu et-al.…”
Section: Whether This Type Of Relationship Extends Beyond Mescs and Hmentioning
confidence: 99%
“…Aside from ageing, there are several factors that bring about premature greying, including dietary deficiencies 5 , disorders such as alopecia areata or vitiligo 6,7 , and stress 8,9 . Zhang et al set out to test the role of stress in the greying process in mice.…”
mentioning
confidence: 99%